Advanced Numerical Methods for Solving ODEs: An Overview (International Journal of Food and Nutritional Sciences, 2022)
Numerical methods for solving ordinary differential equations (ODEs) are essential tools in various scientific and engineering disciplines. This paper provides an overview of advanced numerical methods, focusing on techniques such as Runge-Kutta, Adams-Bashforth, and implicit/explicit schemes. These methods are crucial for solving ODEs that arise in physics, chemistry, biology, and economics, where analytical solutions are often unattainable. The importance of numerical methods is highlighted through their applications in fluid dynamics, population modeling, and electrical circuit analysis. This overview also discusses recent advancements and key contributions in the field, offering insights into the development and implementation of these techniques. By exploring both theoretical and practical aspects, this paper aims to provide a comprehensive understanding of advanced numerical methods for solving ODEs.